Automated extraction of conducted emission relevant parameters in the case of a DC motor - Weigel, Robert; Leibinger, Árpád; Giese, M. (International Conference on Electromagnetics in Advanced Applications, 2011)
The analysis of the EMC (electromagnetic compatibility) behavior of products is needed nowadays in early project stages. Automation of EMC analysis in the case of systems with high complexity is crucial, because of the high number of parameters and extensive mechanisms of interaction. Systematic methods, however, can find the system parameters which dominate the behavior. Such procedures can be automated, thereby simultaneously speeding up the process and reducing the risk of errors. This paper gives a solution for the automated EMC analysis and optimization of devices using the simulator SABER. The emission was simulated according to the measurement standard CISPR 25. The parameters with the greatest influence on emission characteristics can be extracted from the parameters of system elements in a circuit simulation model by this proposed method based on global sensitivity analysis.
elib2cris::1512001600,weigel2011f
Keywords: DC motors; electromagnetic compatibility; CISPR 25; SABER; automated EMC analysis; circuit simulation model; device optimization; electromagnetic compatibility